Laboratory adapted Escherichia coli K‐12 becomes a pathogen of Caenorhabditis elegans upon restoration of O antigen biosynthesis. Issue 5 (28th January 2013) - Browning, Douglas F.; Wells, Timothy J.; França, Fernanda L. S.; Morris, Faye C.; Sevastsyanovich, Yanina R.; Bryant, Jack A.; Johnson, Matthew D.; Lund, Peter A.; Cunningham, Adam F.; Hobman, Jon L.; May, Robin C.; Webber, Mark A.; et al.
Summary Escherichia coli has been the leading model organism for many decades. It is a fundamental player in modern biology, facilitating the molecular biology revolution of the last century. The acceptance of E. coli as model organism is predicated primarily on the study of one E. coli lineage; E. coli K‐12. However, the antecedents of today's laboratory strains have undergone extensive mutagenesis to create genetically tractable offspring but which resulted in loss of several genetic traits such as O antigen expression. Here we have repaired the wbbL locus, restoring the ability of E. coli K‐12 strain MG1655 to express the O antigen. We demonstrate that O antigen production results in drastic alterations of many phenotypes and the density of the O antigen is critical for the observed phenotypes. Importantly, O antigen production enables laboratory strains of E. coli to enter the gut of the Caenorhabditis elegans worm and to kill C. elegans at rates similar to pathogenic bacterial species. We demonstrate C. elegans killing is a feature of other commensal E. coli. We show killing is associated with bacterial resistance to mechanical shear and persistence in the C. elegans gut. These results suggest C. elegans is not an effective model of human‐pathogenic E. coli infectious disease.